The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1149/2.0341507jes
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Corrosion of Mg Alloy AZ91D Fabricated by a Semi-Solid Casting Technique: The Influence of Microstructure

Abstract: The atmospheric corrosion behavior of alloy AZ91D produced by a semi-solid metal (SSM) technique and by conventional high pressure die casting (HPDC) was investigated for up to 1176 hours in the laboratory. Alloy AZ91D in the SSM state was fabricated using a rheocasting (RC) technique in which the slurry was prepared by the RheoMetal process. Exposures were performed in 95% RH air at 22 and 4 • C. The RC alloy AZ91D exhibited significantly better corrosion resistance than the HPDC material at two temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 82 publications
0
24
0
Order By: Relevance
“…Hence, it has been shown that the Al content in α-Mg in alloy AZ91D can be increased by modifying the casting technology, resulting in improved corrosion properties. 62 The presence of ppb levels of ozone and NO 2 strongly increases the SO 2 deposition on AZ91D at 60% RH (see Figs. 9 and 10).…”
Section: Discussionmentioning
confidence: 96%
“…Hence, it has been shown that the Al content in α-Mg in alloy AZ91D can be increased by modifying the casting technology, resulting in improved corrosion properties. 62 The presence of ppb levels of ozone and NO 2 strongly increases the SO 2 deposition on AZ91D at 60% RH (see Figs. 9 and 10).…”
Section: Discussionmentioning
confidence: 96%
“…Based on the reasons presented in the Introduction, it is highly desirable to produce Mg-based MMC cast components with uniform reinforcement distribution and structural integrity. The RC method in combination with the RheoMetal process has already established itself as a promising casting technique enabling the production of high-quality and complex cast Mg alloys with enhanced service performances [22,27,28]. Thus, one expected to detect a relatively low fraction of casting pores, in the range of 1e2% of the total examined area, in the RC AM50 and AZ91D alloys (see Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The main microstructural constituents are a-Mg grains surrounded by interdendritic regions (also called eutectic a) and b phase particles (Mg 17 Al 12 ). Owing to the presence of Mn, MgeAl alloys in the AM and AZ series also contain a small amount of h phase particles (Al 8 Mn 5Àx Fe x ) [22,28,29]. Moreover, transient phases such as Mg 5 Al have been reported in the microstructure of MgeAl alloys [28].…”
Section: Rc Az91d and Am50 Microstructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the pH range examined, CO2 speciates to bicarbonate, HCO3 − and carbonate, CO3 2− . These species can react with magnesium and aluminum hydroxides at a neutral to moderately alkaline pH to produce a mixed Mg-Al hydroxycarbonate that confers a slight protective effect [34,35]. These changes in the polarization response indicate a time-dependent passivation process that produces a marginal increase in resistance to localized corrosion.…”
Section: Characterization Of Az31 Response In Chloride-only Solutionsmentioning
confidence: 99%